MODEL PENGEMBANGAN MUTU RANISH PADA SATUAN PENDIDIKAN SEKOLAH DASAR SWASTA - Apriyani, Helina; Nurdin, Diding; Prihatin, Eka (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2023)
Total Quality Management is an approach to an organization that focuses on quality and is based on the participation of all human resources and is aimed at long-term results and success through customer satisfaction and providing benefits to members of the organization. The main customers in this study are students and parents. The National Standards contained in PP No. 57 of 2020 have set national quality standards for education. Quality improvement in schools is the responsibility of all school members. In addition, the teacher is an important key in improving classroom learning which will later have an impact on improving the quality of education. All resources and efforts have been made in the process of improving the quality of schools, one of which is the application of sustainable national education standards. Furthermore, there is continuous TQM. In the development of models in achieving the quality of education is very necessary in the realization of education itself. Given the importance of the implications of quality assurance in the learning process, the RANISH quality development model was designed in the process of improving the quality of education. This research uses qualitative research methods with the DBR (Design Based Research) method approach. The DBR method is felt to be very suitable because the DBR method aims to provide solutions to any problems that arise and is relevant in order to develop a quality development model in educational units because it is able to bridge theory and practice. The recommendations for the RANISH quality development model are felt to be appropriate because they are based on precise and measurable quality control. Starting with the process of quality planning, quality control and quality improvement.